Feasibility of using patient-facing technology for the identification of COPD in primary care. Issue 2 (1st April 2016) - Ahern, David K.; Parker, Donna R.; Eaton, Charles B.; Rafferty, Caitlin; Wroblewski, Joseph; Goldman, Roberta
Abstract : The proliferation of mobile devices and emergence of interoperable 'mHealth' apps is accelerating development and deployment of patient-facing risk assessments in primary care. The present study describes a user-centered design and an agile development approach to creation of an app for assessing lung function as part of a randomized controlled trial for the identification of chronic obstructive lung disease in primary care. Seventeen patients recruited from a hospital-based, ambulatory family medicine clinic agreed to be videotaped while using the app, Lung Age, on a first-generation iPad prior to their provider encounter. Subsequently, participants were interviewed using a semi-structured interview guide upon exiting their medical visit. Observational data indicated that participants took advantage of the portability and flexibility of the tablet device in the exam room to engage with the Lung Age app with the option to share and discuss their results with their providers. Results from the semistructured interviews indicated that participants perceived the Lung Age app as intuitive and easy to use. These results demonstrate that tablet computers and mHealth apps can be used to deploy acceptable and useable electronic risk assessments in primary care settings. Future research focused on the impact and outcomes of patient-centered, mHealth apps for risk screening in primary care is warranted.